Continuance intention of Learning Management System (LMS) among lecturers in northern polytechnic, Malaysia - Nor Ashikin, Mohamad Isa (2020)
This study aims to determine the factors influencing continuance intention of LMS among lecturers in northern polytechnic, Malaysia. This study use four elements of Unified Theory of Acceptance and Use of Technology (UTAUT): Performance Expectancy, Effort Expectancy, Social Influence and Facilitating Condition to determine the impact of continuance intention of LMS. One element, Self-Efficacy was also added to identify the continuance intention of LMS among lecturers in northern polytechnic, Malaysia. Furthermore, this study is intended to examine the relationship and effect between continuance intention of LMS and factors influencing the usage of LMS. A total of 248 polytechnic lecturers from three Northern Polytechnic have participated in this study. Self-administrated survey questionnaire has been used to collect all variables data. The result of Multiple Regression analysis indicated that social influence, facilitating condition, and self-efficacy significantly affect the continuance intention to use LMS among lecturers in northern polytechnic. However, performance expectancy and effort expectancy showed insignificant influence towards the continuance intention. Among all predictors, facilitating condition has the strongest influence on the continuance intention to use LMS among lecturers in northern polytechnic. This study concludes with a discussion of the research findings, theoretical and practical contribution, limitation of the study and suggestion for future research.